Fracturing Pressure of Shallow Sediment in Deep Water Drilling. (24th August 2013) - Yan, Chuanliang; Deng, Jingen; Hu, Lianbo; Yu, Baohua
Abstract : The shallow sediment in deep water has weak strength and easily gets into plastic state under stress concentration induced by oil and gas drilling. During drilling, the formation around a wellbore can be divided into elastic zone and plastic zone. The unified strength theory was used after yielding. The radius of the plastic zone and the theoretical solution of the stress distribution in these two zones were derived in undrained condition. The calculation model of excess pore pressure induced by drilling was obtained with the introduction of Henkel's excess pore pressure theory. Combined with hydraulic fracturing theory, the fracturing mechanism of shallow sediment was analyzed and the theoretical formula of fracturing pressure was given. Furthermore, the influence of the parameters of unified strength theory on fracturing pressure was analyzed. The theoretical calculation results agreed with measured results approximately, which preliminary verifies the reliability of this theory.